An Approach Based on Conceptual Modeling to Understand Factors that Influence Interoperability in Systems-of-Information Systems - Fernandes, Juliana; Graciano Neto, Valdemar Vicente; dos Santos, Rodrigo Pereira (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2021: Anais do XX Simpósio Brasileiro de Qualidade de Software, 2021)
Systems-of-Information Systems (SoIS) are alliances of independent information systems interoperating to accomplish a set of goals. The establishment of interoperability links is a challenge due to multiple aspects, such as the needs related to (i) planning and design of the system arrangement, orchestrating them to have their outputs and inputs connected to exchange data or reconfigured in order to keep the services being provided, (ii) provision of technical solutions to make heterogeneity transparent and to effectively mediate the systems, and (iii) establish new links so that they impact on the business and human involved. This Master's thesis presents a set of contributions based on studies that characterize the SoIS scenario. More specifically, this work focuses on investigating technical, human, and organizational factors that impact the design of interoperability links in this scenario. The factors that influence interoperability are relevant to the quality of software products involved in system arrangements, given its support decision-making related to settings of interoperability links, especially at the organizational level.